2021
DOI: 10.1097/rct.0000000000001219
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Benefit Evaluation: Application of Multiphase Computed Tomography Angiography in Mechanical Thrombectomy for Patients With Acute Ischemic Stroke

Abstract: Objective:The objective of this study was to evaluate the collateral circulation in patients with acute ischemic stroke (AIS) by multiphase computed tomography angiography (mCTA) and explore its application value in the risk and benefit assessment after thrombectomy.Methods: Clinical and imaging parameters of AIS patients who underwent thrombectomy were consecutively collected. The 90-day modified Rankin Scale (mRS) score was used as the standard for evaluating the recovery of neurological functions. The recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The mRS score reflects the cerebral function, and thus, its improvement may have resulted from enhanced blood perfusion. Previous studies have demonstrated a significant correlation between the mRS score and blood distribution in several neurological deficits, including subarachnoid haemorrhage ( 24 ), acute ischemic stroke ( 25 ) and symptomatic intracerebral haemorrhage ( 26 ). In addition, compared with the mRS score 1 week after surgery, the mRS scores decreased 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The mRS score reflects the cerebral function, and thus, its improvement may have resulted from enhanced blood perfusion. Previous studies have demonstrated a significant correlation between the mRS score and blood distribution in several neurological deficits, including subarachnoid haemorrhage ( 24 ), acute ischemic stroke ( 25 ) and symptomatic intracerebral haemorrhage ( 26 ). In addition, compared with the mRS score 1 week after surgery, the mRS scores decreased 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the prodromal and early stages of AIS, patients' overall prognoses and mortality rates vary greatly due to factors such as the imaging evaluation, mode of prehospital transport, and level of emergency treatment provided. 2 Since 2015, AIS due to large vessel occlusion has been progressively treated with endovascular thrombectomy with intravascular retrievable stent placement, for which prognoses have proved to be better than those for treatment with intravenous recombinant tissue plasminogen activator. After strict case screening, the time window for thrombectomy has been gradually extended from the traditional 6 hours to 16 hours, with some patients still benefitting from this process even 24 hours later.…”
mentioning
confidence: 99%
“…An extensive survey conducted globally found that acute ischemic stroke (AIS), characterized as a sudden onset of diminished cerebral blood circulation, was the second leading cause of death in middle-aged and older adults worldwide, after heart disease 1 . In the prodromal and early stages of AIS, patients' overall prognoses and mortality rates vary greatly due to factors such as the imaging evaluation, mode of prehospital transport, and level of emergency treatment provided 2 . Since 2015, AIS due to large vessel occlusion has been progressively treated with endovascular thrombectomy with intravascular retrievable stent placement, for which prognoses have proved to be better than those for treatment with intravenous recombinant tissue plasminogen activator.…”
mentioning
confidence: 99%